Avaliação do processo oxidativo avançado por permanganato de potássio no tratamento de solos contaminados com idrocarbonetos poliaromáticos - Silva, Celyna Káritas Oliveira da (2010)
The soil contamination with petroleum is one of the major concern of industries operating in the field and also of environmental agencies. The petroleum consists mainly of alkanes and aromatic hydrocarbons. The most common examples of hydrocarbons polyaromatic are: naphthalene, anthracene, phenanthrene, benzopyrene and their various isomers. These substances cause adverse effects on human and the environment. Thus, the main objective of this work is to study the advanced oxidation process using the oxidant potassium permanganate (KMnO4) for remediation of soils contaminated with two polyaromatic hydrocarbons (PAHs): anthracene and phenanthrene. This study was conducted at bench scale, where the first stage was at batch experiment, using the variables: the time and oxidant dosage in the soil. The second stage was the remediation conducted in continous by a fix column, to this stage, the only variable was remediation time. The concentration of oxidant in this stage was based on the best result obtained in the tests at batch, 2,464 mg / L. The results of degradation these contaminants were satisfactory, at the following dosages and time: (a) 5g of oxidant per kg soil for 48 hours, it was obtained residual contaminants 28 mg phenanthrene and 1.25 mg anthracene per kg of soil and (b) for 7g of oxidant per kg soil in 48 hours remaining 24 mg phenanthrene and anthracene 0.77 mg per kg soil, and therefore below the intervention limit residential and industrial proposed by the State Company of Environmental Sao Paulo (CETESB)